2021
DOI: 10.18700/jnc.210007
|View full text |Cite
|
Sign up to set email alerts
|

Role of continuous hypertonic saline in acute ischemic infarcts: a systematic literature review

Abstract: Continuous hypertonic saline for hemispheric ischemic infarcts has been routinely used in neurocritical centers for the management of malignant cerebral edema. However, the data supporting its use are extremely limited. We present a systematic literature review that highlights five studies (one randomized control trial and four retrospective cohort) where the effects of continuous hypertonic saline were studied in patients with acute ischemic infarcts. Collectively, there is a lack of substantial evidence supp… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0
1

Year Published

2023
2023
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 19 publications
0
1
0
1
Order By: Relevance
“…42 A systematic review by Chugh et al on the effects of continuous HTS therapy in patients with acute ischemic infarcts, concluded that although HTS administration demonstrated improvement in the ICP, there was no significant improvement in the mortality and neurological/functional outcomes. 43…”
Section: Clinical Uses Of Hypertonic Salinementioning
confidence: 99%
“…42 A systematic review by Chugh et al on the effects of continuous HTS therapy in patients with acute ischemic infarcts, concluded that although HTS administration demonstrated improvement in the ICP, there was no significant improvement in the mortality and neurological/functional outcomes. 43…”
Section: Clinical Uses Of Hypertonic Salinementioning
confidence: 99%
“…렵고, 그에 따라 뇌압조절에 실패하게 된다 [5][6][7][8]. 따라서 이 논문에서는 만니톨과 고장성 식염수를 사용하면서 발생할 수 있는 대표적인 부작용을 이해하고, 부작용을 최소화하면서 고삼투압 치료를 할 수 있는 방법에 대해 알아보고자 한다.…”
unclassified